Sallèles-d'Aude Un complexe de potiers gallo-romain : le quartier artisanal - Laubenheimer, Fanette (Documents d'archéologie française, 1990)
Since 1976 the Sallèles-d'Aude site has been the scene of extensile excavations in the context of research on the production of amphorae in Roman Gaul Prospection and excavations, which are still under way. Have uncovered a pottery complex including a dwelling area and a workplace, which is the subject of this hook showing all phases of pottery production over a period lasting from the 1st to the IIIrd century A D The stratigraphy and the architecture of the workshops. The spatial organization and the production are all examined in turn A study of the production provides references on origins and chronology for a wide range of ceramic products destined for building, cooking, food storage and the packing of foodstuffs for sale. This work, essential for those specialising in pottery workshops and the crafts and economy of Southern Gaul, goes beyond this framework and is of interest to all specialists in the Roman world.